Answer:
There are many, many, different expressions equivalent, but if you distribute them together you come up with:
8x² - 22x + 15
Explanation:
When distributing (4x–5) (2x-3) we should end up with four values, and then add them together.
[] The outside numbers of 4x and -3
-> 4x * -3 = -12x
[] The inside numbers of -5 and 2x
-> -5 * 2x = -10x
[] The left numbers of 4x and 2x
-> 4x * 2x = 8x²
[] The right numbers of -5 and -3
-> -5 * -3 = 15
Now we can add them together;
-12x + -10x + 8x² + 15
8x² - 22x + 15
Have a nice day!
I hope this is what you are looking for, but if not - comment! I will edit and update my answer accordingly.
- Heather